Maternity leave - Ali Hassan Humaid Alhosani, Adnan; Johar, Siti Sarawati; Ismail, Fadillah (Penerbit UTHM, 2020)
A numerous off-days which a woman is legally approved to be absent from work in the weeks prenatal and postnatal recovery phase after giving birth defines maternity leave. It is stated that at least 60 consecutive days of paid maternity leave were entitled to all female workers in Malaysia if they have worked at least 90 days with their current employers in four months leading up to their confinement period, except for exempted categories (Employment Act 1955) During the maternity leave, female workers are entitled to be provided with all relevant contractual benefits and paid with full salary as if they are in an active employment excluding the benefits that are tied to active work. The right to resume working upon their return from maternity leave is also protected.